2000
DOI: 10.1645/0022-3395(2000)086[0838:dfocpi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fingerprinting of Cryptosporidium parvum Isolates Using Amplified Fragment Length Polymorphism (AFLP)

Abstract: The genetic variability of 10 Cryptosporidium parvum isolates of human and animal origin was investigated using amplified fragment length polymorphism (AFLP). Analysis of fluorescent dye-labeled amplified products was carried out using an ABI PRISMS 377 DNA sequencer and ABI PRISMS GeneScan software. One-hundred and twelve primer combinations were evaluated using a single C. parvum isolate. The patterns generated were highly reproducible. For subsequent study, a subset of 9 primer pairs that yielded 30-90 DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Isolates WH33 and WH37 were identical to Cryptosporidium genotype W17 deposited in GenBank (GenBank accession number AY737573 [13]). WH3 was identical to cervine genotype sequences (GenBank accession numbers AY737592 [13], AJ849465, and AF442484 [4]), while WH5 was a variant of the cervine genotype that differed by an AT deletion at positions 689 and 690 of the C. parvum 18S rRNA gene (GenBank accession number AF164102 [2]) (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
“…Isolates WH33 and WH37 were identical to Cryptosporidium genotype W17 deposited in GenBank (GenBank accession number AY737573 [13]). WH3 was identical to cervine genotype sequences (GenBank accession numbers AY737592 [13], AJ849465, and AF442484 [4]), while WH5 was a variant of the cervine genotype that differed by an AT deletion at positions 689 and 690 of the C. parvum 18S rRNA gene (GenBank accession number AF164102 [2]) (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
“…It consists of four steps: DNA digestion, ligation, amplification, and gel analysis. Polymorphisms are identified based on the presence or absence of DNA fragments by polyacrylamide gel analysis (7). The advantages of this technique are the ability to search an entire genome for polymorphisms, the reproducibility of the method, and the possibility of being used against parasites about which there is no prior genetic information (7,77,78).…”
Section: Amplified Fragment Length Polymorphism (Aflp)mentioning
confidence: 99%
“…Studies have demonstrated its application to differentiate isolates of C. parvum into two distinct genotypes, as well as strains of Leishmania belonging to cutaneous leishmaniosis (CL) and visceral leishmaniosis (VL) (7). Analysis based on AFLP polymorphic markers have revealed high genetic variability among the genome species of Leishmania major, L. tropica and L. donovani, which was sufficient to distinguish between CL and VL (79).…”
Section: Amplified Fragment Length Polymorphism (Aflp)mentioning
confidence: 99%
See 2 more Smart Citations